Application of direct and inverse kinematics and dynamics in motion planning of manipulator links - Delyová, Ingrid; Hroncová, Darina; Frankovský, Peter; Sivák, Peter; Kostka, Ján; Neumann, Vojtech (Zielona Góra: Uniwersytet Zielonogórski)
For the synthesis of manipulators and robots, an accurate analysis of movements of the individual links is essential. This paper deals with motion planning of the effector of a multi-linked manipulator. An important issue in this area is the orientation and position of links and kinematic pairs in space. In particular, attention should be paid to the position of their endpoint as well as other significant points.
Keywords: kinematics analysis; manipulator; inverse kinematics problem; motion planning; inverse dynamics problem